APC Nb3Sn superconductors based on internal oxidation of Nb–Ta–Hf alloys. (1st March 2023) - Xu, X; Peng, X; Wan, F; Rochester, J; Bradford, G; Jaroszynski, J; Sumption, M
Abstract: In the last few years, a new type of Nb3 Sn superconducting composite, containing a high density of artificial pinning centers (APC) generated via an internal oxidation approach, has demonstrated a significantly superior performance relative to present, state-of-the-art commercial Nb3 Sn conductors. This was achieved via the internal oxidation of Nb-4at.%Ta-1at.%Zr alloy. On the other hand, our recent studies have shown that internal oxidation of Nb–Ta–Hf alloys can also lead to dramatic improvements in Nb3 Sn performance. In this work we follow up on this latter approach, fabricating a 61-stack APC wire based on the internal oxidation of Nb-4at.%Ta-1at.%Hf alloy, and compare its critical current density ( J c ) and irreversibility field with APC wires made using Nb-4at.%Ta-1at.%Zr. A second goal of this work was to improve the filamentary design of APC wires in order to improve their wire quality and electromagnetic stability. Our new modifications have led to significantly improved residual resistivity ratio and stability in the conductors, while still keeping non-Cu J c at or above the conductor J c specification required by the proposed Future Circular Collider. Further improvement via optimization of the wire recipe and design is ongoing. Finally, additional work needed to make APC conductors ready for applications in magnets is discussed.